How Financial Literacy Influences Gen Z Investment Decisions through Attitude and Overconfidence - Je Ivan Dhamma Pratama; Christina Yanita Setyawati (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2025)
In this competitive and dynamic era, the financial industry presents new opportunities and challenges. Especially in the investment sector, which has been booming since the Covid-19 pandemic, people are competing to maximise profits in the capital market with minimal risk. To maximise profits, a combination of financial knowledge and appropriate behaviour is needed to grow a portfolio. The increasing participation of Generation Z in the capital market, driven by easy access to digital investment platforms, highlights the importance of financial management education. Such education is essential to help Gen Z manage risk, avoid overconfidence, and make informed investment decisions in an uncertain and technology-driven financial environment. This study aims to examine how overconfidence and financial literacy influence investment decisions. This study involved Gen Z, a generation known for its apathy and dominance in the capital market. The sample size for this study reached 385 respondents. Data collection was conducted using Google Forms. This study tested the coefficient of determination, standard deviation, and data reliability using Cronbach's alpha. Data analysis was performed using SEM (Structural Equation Modelling) with the SmartPLS 4.0 application. The results of the study show that financial literacy has a significant positive effect on investment decisions, attitude has a significant positive effect on investment decisions, overconfidence has a significant positive effect on investment decisions, financial literacy has a significant positive effect on attitude, financial literacy has a significant positive effect on overconfidence, financial literacy has a significant positive effect on investment decisions through attitude mediation, and financial literacy has a significant positive effect on investment decisions through overconfidence mediation.